The Pre-Processing of Images Technique for the Material Samples in the Study of Natural Polymer Composites - Putyatin, Y.; Mohammad, A.; Lyashenko, V.; Khan, A. (AJER, 2016)
The image processing analysis is one of the most powerful tool in various research fields, especially in material / polymer science. Therefore in the present article an attempt has been made for study of pre-processing of images technique of the material samples during the images taken out by Scanning Electron Microscope (SEM). First we prepared the material samples with coir fibre (natural) and its polymer composite after that the image analysis has been performed by SEM technique and later on the said studies have been conducted. The results presented here were found satisfactory and also are in good agreement with our earlier work and some other worker in the same field.
Keywords: composite; image; noise suppression; contrast increase